2016
DOI: 10.1097/mca.0000000000000314
|View full text |Cite
|
Sign up to set email alerts
|

Paclitaxel-coated balloon plus bare-metal stent for de-novo coronary artery disease

Abstract: PCB angioplasty plus BMS was superior to BMS alone for the treatment of de-novo lesions. The combined clinical endpoint was lower with PCB plus BMS at 6 months and remained lower after 5 years. There was no late catch-up phenomenon (http://www.clinicaltrials.gov; NCT 00732953).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 19 publications
0
14
0
Order By: Relevance
“…Data regarding an a priori strategy of BMS + PCB in de novo coronary artery stenoses are still of the PERfECT trial, a randomized study of BMS/ /PCB vs. BMS in de novo stenoses showed superiority for an adjunctive delivery of paclitaxel by a coated balloon for clinical endpoints [10]. O the contrary, another recently published randomized study found an increased stent thrombosis rate for the concept of BMS + PCB compared to the investigating the course of vessel healing after a BMS + PCB approach using QCA and OCT. *1 patient had only an angiographic follow-up without OCT imaging; # 7 lesions (7 patients) were included in both groups due to sequential follow-up and 1 patient was included with 2 study lesions; ISA -incomplete stent apposition; MLD -minimal lumen diameter; OCT -optical coherence tomography; QCA -quantitative coronary angiography; RLD -reference lumen diameter Figure 2.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Data regarding an a priori strategy of BMS + PCB in de novo coronary artery stenoses are still of the PERfECT trial, a randomized study of BMS/ /PCB vs. BMS in de novo stenoses showed superiority for an adjunctive delivery of paclitaxel by a coated balloon for clinical endpoints [10]. O the contrary, another recently published randomized study found an increased stent thrombosis rate for the concept of BMS + PCB compared to the investigating the course of vessel healing after a BMS + PCB approach using QCA and OCT. *1 patient had only an angiographic follow-up without OCT imaging; # 7 lesions (7 patients) were included in both groups due to sequential follow-up and 1 patient was included with 2 study lesions; ISA -incomplete stent apposition; MLD -minimal lumen diameter; OCT -optical coherence tomography; QCA -quantitative coronary angiography; RLD -reference lumen diameter Figure 2.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown inconsistent results regarding the antiproliferative strength of such an adjunctive procedure [5][6][7][8][9][10]. Yet, no data about the time course of arterial vessel response and stent coverage after such a procedure is available.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Therefore, it cannot be considered a true BMS. However, the PERfECT stent study [24, 25] showed that DEB in combination with an EPC stent was better than EPC stent alone; however, these findings were not supported by the PEGASUS study [26]. However, when DEB + BMS are compared to DES, at best similar results have been reported [27], but most studies have found the combination of DEB + BMS inferior to DES.…”
Section: Drug-eluting Balloonsmentioning
confidence: 99%
“…However, bifurcation, in-stent restenosis, and small vessel lesions remain challenging subsets even in the DES era, and DEB angioplasty with bailout stenting has been suggested as an alternative treatment strategy. In this issue of the Journal, the PERFECT (Prospective, Randomized Trial Evaluating a Paclitaxel-Eluting Balloon in Patients Treated with Endothelial Progenitor Cell Capturing Stents for De Novo Coronary Artery Disease) Stent study investigators compared paclitaxelcoated balloon angioplasty plus bare-metal stenting with bare-metal stenting alone in 120 patients with native coronary artery disease [5]. At 5 years of follow-up, the rate of target lesion revascularization was 15 versus 23.2%, respectively (P = 0.26).…”
mentioning
confidence: 99%